Foraging behavior of leaf cutting ants: How do workers search for their food? - Travaglini, R. V. [UNESP]; Forti, L. C. [UNESP]; Camargo, R. S. [UNESP] (Universidade Estadual de Feira de Santana, 2015)
Foraging behavior of leaf cutting ants: How do workers search for their food? Forager ants search for adequate food sources in nature and, after their discovery, they decide whether the source is suitable or not for the colony. However, we asked How do workers seek out the substrate for cultivation of the symbiontic fungus on which they feed? To answer this question, we evaluated the distance traveled by individual workers in the search of food and the distance traveled to return to the nest, as well as the time and velocity necessary for these activities. The results showed that the distance traveled by the leaf cutting ant, Atta sexdens rubropilosa (Linneus, 1758), in the search of food was greater than the distance traveled to return with the substrate to the colony. On the other hand, the mean time and velocity were similar for food search and return to the colony. These results support the hypothesis of information transfer, according to which the worker needs to return to the nest at the beginning of foraging to transfer information to other workers and thus to establish the process of worker ant foraging. It can be concluded that workers travel large distances in a random manner until finding their substrate, but the return to the nest is efficient considering the shorter distance traveled.
Keywords: Atta sexdens rubropilosa; Foraging; Leaf cutting ants